Perspectives on land and water politics at Mushandike Irrigation Scheme, Masvingo, Zimbabwe - Mafukidze, Jonathan (Rhodes University, Faculty of Humanities, Department of Sociology, 2019)
Access to, control and ownership of land and water, amongst other natural resources in Zimbabwe, shape and affect rural lives, livelihoods, social relations and social organisation. Rural poverty has been entrenched and exacerbated by, amongst other factors, highly restricted access to these scarce resources. Historically, Zimbabwe's rural areas (such as communal areas, smallholder irrigation schemes and resettlement areas) have existed as sites of struggles where contestations and negotiations over access to, control or ownership of these resources have taken place. Resultantly, multifaceted and dynamic social relations have been weaved and contested social spaces carved out. In rural Zimbabwe, contestations have tended to be complex, nuanced and intricate, working themselves out in different ways across time and space. In their heightened and more visible state, they have been characterised by violent physical expressions which, in the history of the country, involved two wars of liberation, the First Chimurenga (1896-1897) and the Second Chimurenga (1960s to 1980). The most recent violent manifestation was through nation-wide land invasions, politically christened the Third Chimurenga, which peaked in 2000 and continued sporadically to this day. Few studies on smallholder irrigation schemes in Zimbabwe have focused on understanding how contestations for access to scarce land and water resources are framed and negotiated at the local level. Cognisant of this lacuna, this thesis uses social constructionism in examining, as a case study, Mushandike Smallholder Irrigation Scheme in Masvingo Province in order to understand and analyse how land and water politics occur at the local level. The study deploys a qualitative research methodology approach in examining local water and land politics, which involved original irrigation beneficiaries and more recent land invaders. Findings of the thesis indicate that land and water shortages have increased considerably in the past two decades at the irrigation scheme due to the influx of land invaders into the scheme. This influx has had a negative impact on agricultural production and other livelihood strategies. Both scheme members and land invaders lay claim to land and water at Mushandike. These claims are intricately constructed and contested, and they are linked to broader issues such as partisan party-politics, policy developments, and tradition, origin, indigeneity and belonging. Though the struggles over land and water at Mushandike are firmly rooted in the concrete conditions of existence and experiences of beneficiaries and land invaders, external actors such as political leaders, state bureaucrats and traditional chiefs tend to complicate and intensify the contestations.
Keywords: Uncatalogued